Assessing CeO2 and TiO2 Nanoparticle Concentrations in the Seine River and Its Tributaries Near Paris - Phalyvong, Karine; Sivry, Yann; Pauwels, Hélène; Gélabert, Alexandre; Tharaud, Mickaël; Wille, Guillaume; Bourrat, Xavier; Ranville, James F.; Benedetti, Marc F. (Frontiers in Environmental Science, 2021)
Motivation for detecting engineered nanoparticles (ENPs) in the environment comes from a need to understand fate and behavior of these materials in natural matrices. The difficulty lies in the low expected ENP particle number concentration (PNC) and the presence of a large and variable background concentration of natural NPs. We report the PNCs and characteristics of cerium-bearing nanoparticles (Ce-NPs) and titanium-bearing nanoparticles (Ti-NPs) in an aquatic matrix (the Seine River and three of its tributaries) with the use of single particle ICP-MS (spICPMS) and electron microscopy (FEG-SEM). Ce-bearing and Ti-bearing particles were observed in suspended particulate matter collected onto 0.2 µm and1 kDa filters, using FEG-SEM imaging. At Marnay-sur-Seine, the upstream point, PNCs for Ce-NPs and Ti-NPs were 0.47 ± 0.07 x 106 and 1.35 ± 0.17 x 106 particles as measured by spICPMS. The maximum PNC for both Ce-NPs and Ti-NPs, 1.59 ± 0.10 x 106 particles mL-1 and 5.89 ± 0.10 x 106 particles mL-1 respectively, are found in the Marne River, a major tributary to the Seine. It was shown that downstream of each confluence, an increase in the PNC of the Seine is observed, suggesting a significant contribution of the different tributaries. Mass balance of particles flows and elemental ratios of Ce/La showed that in the Marne and the Oise River, a contribution of natural CeO2 NPs exists. The anthropogenic contribution in TiO2 ENPs for the Marne River was further assessed with other elemental ratios (Ti/V and Ti/Y). Near constant element ratios in the Seine below the Orge River and Paris city suggest neither contribute significantly to Ce or Ti NP concentrations. The study provides further investigation of the strengths and limitations of the application of spICPMS to natural samples and contributes data to the currently highly-limited dataset on natural NP backgrounds in rivers, information that is key to assessing the potential for quantifying the input of ENPs to surface waters. Of the total mass of Ce and Ti, 83% and 90% respectively, could be detected as particles by spICPMS.